Peran Organisasi Persaudaraan Setia Hati Terate (PSHT) Dalam Membentuk Karakter Remaja Di Desa Maktihan Kecamatan Malaka Barat Kabupaten Malaka. - Seuk, Stevania; Famdale, Rongky Y; Selly, Frans Kristian (Universitas Nusa Cendana, 2025)
PSHT organization or otherwise known with SH Terate is something fraternity / college purposeful martial arts educate And form virtuous human _ sublime , you know Correct And Wrong . Role played _ PSHT organization in the Desa Maktihan Kabupaten Malaka, and description character para teenager before follow PSHT organization has character hard head or resistance behavior , like _ make riot , make trouble in environment , drinking alcohol. Study This aim For know Role Organization Brotherhood Loyal Heart Terate (PSHT) In Shaping Character Teenagers in the Desa Maktihan, Research This use method qualitative descriptive research carried out in the Desa Maktihan. As for technique data collection used in study This is interviews , observations And studies documentation . Based on results study concluded that Roles / activities carried out PSHT organization exists three that is help fellow PSHT members when experience grief , naibete cup and help public when experience disaster natural / flood . With activity This done can form character teenager like not quite enough responsibility , independence , leader , and unity . Advice, should be expand basic programs values character like religious , democratic , enthusiastic nationality , and Love homeland , so PSHT students / teenagers have values character the .